Bumi Hangus Pangkalan Brandan: Dari Eksploitasi Minyak Bumi hingga Aksi Revolusioner di Sumatera Timur, 1947 - Sumantri, Pulung; Gultom, Adam Zaki (Warisan: Journal of History and Cultural Heritage, 2020)
This article discusses the scorched earth tragedy that occurred in Pangkalan Brandan during the Indonesian independence revolution. Pangkalan Brandan is an area that is included in the territory of the Sultanate of Langkat. Before being managed by a foreign company, the oil mines in this area were managed by the local community in a traditional way. However, after the discovery of new oil wells in Telaga Said and Telaga Tunggal by the Dutch East Indies company Koninklijke Nederlandsche Maatschappij tot Exploitatie van Petroleumbronnen in Nederlandsch Indie, the management of Brandan petroleum was managed in a modern way. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, based on library research related to the topic under study. At the end of the Dutch East Indies rule, the Brandan petroleum mine was burned by the Dutch due to the imminent arrival of Japanese troops. Then after being controlled by Indonesia, there was another scorching of the Pangkalan Brandan oil refinery carried out by fighters and the surrounding community. This terrible tragedy is still celebrated as the "Scorched Earth Pangakalan Brandan" event.